Vulneración del Derecho a la Intimidad: Análisis Jurídico y Doctrinario en el contexto de incautación de dispositivos tecnológicos por parte de Fiscales y Policías durante la instrucción fiscal - Valdez Vidal, Dayana Fernanda (2024)
The present research aims to study the legal and doctrinal aspects of the violation of the right to privacy in the context of the seizure of technological devices. This is conceived apart from guarantee the due process of such interventions, which involves a right and its potential violation to a legally protected good, such as the right to privacy, although among the powers of the holder of the exercise of public criminal action, among others, is that of collecting evidence, elements of conviction that will allow him to objectively support an accusation, considering that when trying to obtain information contained in digital media, not having an express guideline or rule that delimits the extraction of a certain type of information pertinent to the type of investigation, implies a violation of one of the fundamental rights of the person. Subject to an investigation, this legal problem has an impact on the current postulates of the adversarial accusatory system, therefore I will contribute to generating an alternative solution with the propositional guidelines to the legal problem posed. Regarding the methodology, a qualitative approach was applied, allowing for the collection of precise information on the seizure process and its relationship with the right to privacy and possible violations. Additionally, a series of methods were utilized, including the analytical-synthetic, inductive, deductive, and statistical methods, along with instruments such as literature review, survey, and interview, applied to practicing lawyers and judges, respectively. Contrast and verification of the objectives, conclusions, recommendations and propositional guidelines as an alternative and solution to the problem raised.